Influence of anthesis and silking synchronization of maize grain yield across different agroecological conditions - Drašković Bojan; Hojka Zdravko; Knežević Dragan; Šućur Rada; Banjac Borislav; Feher Teodora; Mladenov Velimir (Selekcija i Semenarstvo)
An important goal of maize breeders has been to enhance the stability of maize performance when exposed to different kinds of abiotic stresses. The objective of this study was to evaluate genotype response for reduced anthesis-silking interval (ASI) across nine locations in Romania, Hungary, Croatia, and Serbia under drought and favorable conditions, while eight environments were exposed to heat and drought stress. Field experiments with a two-factorial randomized complete block design were established in 2022, with three replications and 28 hybrids. Seven traits were analyzed in this research: days female end, days of synchronization F-M, days of tasseling, grain dry content, grain dry yield (15% wet), general impression and grain matter content. Mutual correlations were established for all examined traits in all localities, ranging from -0.788 between the traits general impression and grain dry content to 0.978 between the traits general impression and days female end (at the Szekkutes site). Due to the importance of this kind of research, it is necessary to extend the duration of trials to increase accuracy in evaluating abiotic stresses and their effects on fecundation and grain yield.